Analisis comparativo de estabilidad acelerada y estabilidad a largo plazo de jarabe de clenbuterol clorhidrato en envase de polietileno tereftalato (pet) - Jara Solorzano, Seini Evelyn (2010)
In this paper we conducted a comparative analysis of accelerated stability study and the study of long-term stability of a syrup container Clenbuterol hydrochloride in polyethylene terephthalate (PET), to verify that the lifetime of a drug can predict an accelerated stability study. This study was performed by high performance liquid chromatography method (HPLC), according to internal technique for the quantification of clenbuterol hydrochloride syrup, given by ELIFARMA SA Laboratories. The storage conditions were assessed for climate zone IVa and the variables analyzed in samples of Clenbuterol hydrochloride syrups were: appearance, color, smell, taste, pH, concentration of drug and microbiological analysis. For the F-test for variances of two samples and two-sample t test assuming unequal variances were compared and found that the results obtained in the accelerated and long-term study were similar for all analyzed variables, so it follows that both are significant for determining the behavior of a product. According to data obtained after making the long-term study found that the accelerated stability is a reliable method to predict the lifetime of Clenbuterol hydrochloride syrup. It was noted during the study, time and temperature are factors influencing the behavior and life in a product as the concentration increases as the time is reduced, being observed in the samples subjected to 40 ° C and 30 ° C showed a decrease in the concentration of active ingredient, the most significant being the first to mention.